To Compare the Mean Postoperative Pain between Manual Dilatation of Anus and Lateral Internal Sphincterotomy - Muhammad Ahmad, Amna Faiz, Kousar Ramzan, M. Qausain Abu Baker, Muzamil Hazoor Malik, Muhammad Jamahed, Samia Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the mean post-operative pain between manual dilatation of anus and lateral internal sphincterotomy in the treatment of acute anal fissure. Study design: Randomized Controlled Trial Settings: Department of General Surgery, Bahawal Victoria Hospital, Bahawalpur Study duration: 4th October 2020 to 3rd April 2021. Methods: Total 88 patients with acute anal fissure, 30-70 years of age of both genders were selected. Patients with secondary hemorrhoids as a result of abdominal malignancy, anorectal deformity, hypotonic sphincter, underwent previous anorectal surgery, previous anal sphincterotomy or anal dilatation, hemorrhoids, proctitis, abscess, perianal sepsis, proctalgia fugax and fissure were excluded. In group A patients, lateral internal sphincterotomy with open technique was done. Patients in group B were undergone manual dilatation of anus under general anesthesia. Results: The mean age of women in group A was 46.73±8.58 years and in group B was 46.86±10.26 years. Majority of the patients 65(73.86%) were between 25to 40 years of age. Out of 88 patients, 60(61.18%) were males and 28 (38.88%) were females with male to female ratio of 2.1:1. In my study, mean postoperative pain after 10th day was 0.80±0.73 after lateral internal sphincterotomy vs 2.20 ±0.85 after manual dilatation of anus with p-value of 0.0001. Conclusion: This study concluded that the postoperative pain after lateral internal sphincterotomy is less as compared to manual dilatation of anus in the treatment of acute anal fissure.